Transfer from long-term care to acute care and risk of new permanent cognitive or physical disability among long-term care residents in Canada: protocol for a retrospective cohort study - Sharon Kaasalainen; Daniel I McIsaac; Steven Hawken; Daniel Kobewka; Peter Tanuseputro; Amy Hsu; Robert Talarico; Colleen Webber; Ramtin Hakimjavadi; Celeste Fung; Mary M Scott; Doug Manuel; et al. (BMJ Open)
Introduction Long-term care (LTC) residents are frequently transferred to acute care hospitals. Transfer decisions should align with residents’ wishes and goals. Decision to transfer to hospital, when not aligned with the resident’s wishes, can result in transfers that are harmful to residents, leaving residents in a state of disability that could be considered worse than death. We aim to examine whether transfer to an acute care hospital is associated with subsequent new onset of severe permanent physical and cognitive disability in LTC residents.Method and analysis We will conduct a retrospective cohort study of all LTC residents ≥65 admitted to LTC homes between 1 April 2013 and 31 March 2018 in Ontario, Canada. We will use health administrative data from the Continuing Care Reporting System (CCRS), National Ambulatory Care Reporting System (NACRS) and Registered Persons Databases (RPDB), which include data on emergency department visits, hospitalisations, demographic information and mortality. All participants will be followed until 31 March 2023. The exposure is any transfer from LTC to an emergency department or acute care hospital. The outcomes are (1) subsequent new permanent physical disability, (2) subsequent new permanent cognitive disability and (3) all-cause mortality. Due to the time-varying nature of the exposure and confounders, we will use an extended cause-specific Cox regression model to explore this relationship. We will fit marginal structural models (MSMs) to account for the known shortcomings of traditional regression modelling, such as collider bias. Lastly, we will use a preference-based instrumental variable approach to address unmeasured confounders.Ethics and dissemination Ethics approval was obtained through Bruyère Research Institute Ethics Committee (REB#M16-23-030). Study findings will be submitted for publication in a peer-reviewed journal. Findings will be disseminated in conferences and seminars.Trial registration Open Science Framework (https://doi.org/10.17605/OSF.IO/JCDEY).